Spectrum of Maternal Red Cell Alloantibodies Identified in Pregnant Mothers in Perak State Hospital and the Neonatal Outcomes. - Roswati MN; Hasnah Mubeswar; Devin Kumar AK; Hussain RA Saadi; Sabariah Mohd Noor (Asian Journal of Medicine & Health Sciences, 2023)
Red cell alloimmunization during pregnancy results from exposure to foreign red cell antigens due to fetomaternal hemorrhage or blood transfusions. Such alloantibodies can lead to hemolytic disease of the fetus and newborn (HDFN). This study sought to explore the prevalence and range of red cell alloantibodies among pregnant mothers at Hospital Raja Permaisuri Bainun (HRPB) and assess the perinatal outcomes associated with these pregnancies. Conducted over a period spanning from January 2016 to June 2020, this retrospective cross-sectional study was situated within the Transfusion Medicine Department (TMD) of HRPB. Data were sourced from TMD's database and the Hospital Information System (HIS), encompassing all registered pregnant women and their corresponding blood samples. Every antenatal mother underwent routine ABO and RhD typing, as well as the 3-screen red cell panel test. Additionally, antibody identification was performed on the blood samples of patients and referrals that tested positive for alloantibodies.The study findings disclosed that, out of the 467 mothers examined, 1.2% exhibited red cell alloantibodies. The majority of these mothers were of Malay ethnicity, followed by Indian mothers. Among them, 88.9% had a single antibody, while 11.1% had multiple alloantibodies. Clinically significant antibodies were observed in 58% of cases, with antiD (31.7%), anti-E (11.3%), and anti-c (2.1%) being the most prevalent. Anti-Mia was the most frequently occurring non-clinically significant antibody, at 12.6%. Out of the 467 pregnancies, 363 had available outcomes, with 68.0% of newborns displaying jaundice, while 32.0% did not. Newborns born to mothers with clinically significant antibodies had an elevated risk of pathological jaundice (43.6%). Severe and lethal hemolysis cases were predominantly associated with RhD blood antigens, especially anti-D and anti-c.In conclusion, this research highlights the importance of early antenatal screening for alloantibodies, where prompt identification should be conducted to mitigate the risks associated with these antibodies.